Transport of molybdenum with Alamine 336 using supported liquid membrane - Marchese, Jose (2004)
The appropriate experimental conditions of Mo(VI) ion transport across a supported liquid membrane containing Alamine 336 as the mobile carrier dissolved in kerosene solvent have been investigated. The molybdenum flux has been studied as a function of the extraction solution acidity, the sodium carbonate concentration in the stripping solution and the carrier concentration in the liquid membrane. Suitable conditions for both feed and stripping solutions were achieved from analysis of experimental results of molybdenum transport through the liquid membrane. The permeation experiments showed that, at pH 2 with sulfuric acid in the extraction solution and at pH 11.5 with Na2CO3 in the stripping solution, an efficient transfer of the metal ion can be obtained. Furthermore, a maximum molybdenum transport was achieved at around 0.02 M of Alamine carrier in the organic phase. From these results, the extraction-stripping interface reactions for Mo(VI) permeation are proposed. An equation describing the permeation rate, taking into account the aqueous stagnant layers and liquid organic resistance as simultaneous controlling factors, has been derived. The validity of this model is evaluated with experimental data of mass transfer coefficient measured at different stirring rates.